Development of highly sensitive and long-term stable hydrogen sensor for on line monitoring of transformer insulating oil - Park, Jihoon; Lee, Moonhwan; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2020)
Dissolved hydrogen gas analysis is an important method that can define the operational status of a transformer and is vital to the maintenance of safety standards in power grid systems. In this report, a highly sensitive and long-term stable hydrogen sensor system was developed for on line tracing of hydrogen concentration in transformer insulating oil using the wheatstone bridge circuitry with two sensing resistances in a single system and an Al2O3 hydrogen diffusion barrier layer. The two sensing films in this system have the same material, shape, and resistance value to eliminate ambient temperature variation that occur during operation, and palladium (Pd) was used as the sensing material. Experimental tests were fulfilled in airborne gas chamber using the fabricated sensor, resulting in a high sensitivity of 0.0113 mV/ppm and a great linearity of 0.988. The equivalent output voltage profile of the sensor exhibited an error margin of 1.69 % for five cycles at 800 ppm. In experimental testing in transformer insulating oil, the sensor also showed high sensitivity and stable repeatability within a hydrogen concentration range between 70 and 3200 ppm. The obtained sensitivities were 0.058 and 0.022 mV/ppm for sensors with initial resistances of 100 ohm and 190 ohm, respectively. The sensor performances were remained constantly over several days in oil under the condition that a constant current and voltage were applied. The fabricated sensor showed excellent response, good repeatability, and long-term stability in oil, and is therefore a promising candidate for monitoring the operational status of power transformers.
Keywords: Experimental testing; Fabricated sensors; Hydrogen concentration; Hydrogen diffusion barriers; Long term stability; Sensing resistances; Temperature variation; Wheatstone bridges; Hydrogen diffusion barrier; Hydrogen sensor; Pd sensitive film; Transformer insulating oil